THE IMPLEMENTATION OF RESTORATIVE JUSTICE IN LAW ENFORCEMENT IN ITS ACCEPTANCE OF LAW ENFORCEMENT (Comparison of Law Application in Bantul Police) - hartanto hartanto; Bambang Tri Bawono; Roni Sulistyanto Luhukay; Gusti Fadhil Fithrian Luthfan; Syafiqurrohman Syafiqurrohman (Jurnal Meta-Yuridis, 2023)
The application of restorative justice at the investigation level based on the Circular Letter of the Chief of the Indonesian National Police Number: SE/8/VII/2018 concerning the Application of Restorative Justice (Restorative Justice) has been widely SE. 08/2018 concerning the Application of Restorative Justice in the context of accelerating the realization of justice, using a comparative study of criminal cases in the Bantul Regional Police; in this study used normative research methods. The application of the Chief of Police's Circular on Restorative Justice in the case of the crime of theft which is an example/case study in the Bantul Police Region in fact cannot be carried out in general (generalization), this is seen from the factor, namely the losses suffered by the victims. Comparison of cases in BP/…/VIII/2020/RESKRIM and BP/…/III/2020/RESKRIM, both efforts were made to resolve restorative justice but some were completed and some were continued, because essentially a case (case) is not necessarily the same exactly. There is also a disparity in the application of restorative justice based on S.E. National Police Chief with Supreme Court Regulation 2 of 2012.